2020
DOI: 10.15252/embr.201948467
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor‐regulated circ FNTA activates KRAS signaling to promote bladder cancer invasion

Abstract: The androgen receptor (AR) has been linked to bladder cancer (BCa) progression, but if this involves circular RNAs (circRNAs) remains unclear. Here, we find that AR alters the levels of circRNA‐FNTA (circFNTA) to increase BCa cell invasion and chemo‐resistance. Mechanistically, AR represses the RNA editing gene ADAR2 via direct binding to its 5′ promoter region to increase circFNTA levels, which then sponges the microRNA miR‐370‐3p to increase the expression of its host gene FNTA. This AR‐mediated ADAR2/circFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…In summary, circRNAs have been thoroughly proven to participate in anticancer drug resistance. We reviewed Ovarian Cancer Cdr1as MiR-1270/SCAI axis Down [156] Bladder Cancer circ_000285 NA Down [157] circFNTA MiR-370-3p/FNTA axis Up [158] Ref Reference…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, circRNAs have been thoroughly proven to participate in anticancer drug resistance. We reviewed Ovarian Cancer Cdr1as MiR-1270/SCAI axis Down [156] Bladder Cancer circ_000285 NA Down [157] circFNTA MiR-370-3p/FNTA axis Up [158] Ref Reference…”
Section: Resultsmentioning
confidence: 99%
“…Chi et al [ 157 ] reported that the serum circ_0000285 level was decreased in cisplatin-resistant bladder cancer patients compared to cisplatin-sensitive bladder cancer patients and that a low circ_0000285 level indicated poor prognosis, suggesting circRNA_000285 as a biomarker for the cisplatin treatment response in bladder cancer. In addition, Chen et al [ 158 ] found that deletion of circFNTA reduces cisplatin resistance in bladder cancer. High expression of circFNTA can activate KRAS signaling via the miR-370-3p/FNTA axis, thereby contributing to cisplatin resistance.…”
Section: Platinum Drugsmentioning
confidence: 99%
“…BC is the second most common cancer of the genitourinary system, ranking 13th in mortality, although mortality rates are rising in most countries. 6,22 Most are transitional epithelial cell carcinomas. The lateral and posterior walls of the bladder are the most common, followed by the trigonometric region and the apical region.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a large number of studies have shown that, in addition to mRNAs, non-coding RNAs also related to drug resistance of cancers, including gastric cancer [33], bladder cancer [34], lung adenocarcinoma [35]. Moreover, in CRC drug resistance studies, it was reported that LINC00957 could increase 5uorouracil resistance and result in poor survival of patients [36], hsa_circ_0079662 was related to oxaliplatin resistance via TNF-α pathway [25], microRNA-375-3p was involved in 5-uorouracil resistance by targeting thymidylate synthase [37].…”
Section: Discussionmentioning
confidence: 99%